Influence of Voice Focus on Oral-Nasal Balance in Speakers of Brazilian Portuguese - Boer, Gillian de; Castro Marino, Viviane Cristina de [UNESP]; Berti, Larissa Cristina [UNESP]; Gradim Fabron, Eliana Maria [UNESP]; Bressmann, Tim (Karger, 2016)
Objectives: This study investigates whether a change in speaking voice focus affects the oral-nasal balance. The investigation was undertaken with different phonetic materials in speakers of Brazilian Portuguese, which features phonological and phonetic vowel nasalization. Methods: Ten females read oral, balanced oral-nasal, and nasal loaded sentences in their normal voice, and with a backward focus and a forward focus. Nasalance scores were collected with a Nasometer 6400. Results: A repeated measures ANOVA of the nasalance scores demonstrated a significant main effect of speaking condition (F(2, 18) = 12.87, p < 0.001). The mean nasalance scores across the stimuli in the backward focus and normal speaking conditions were 36.85% (SD 16.85) and 40.18% (SD 18.02), respectively, both significantly lower than the forward focus condition at 45.38% (SD 18.90). Conclusion: The results demonstrated that speaking focus influences oral-nasal balance in normal speakers. In future research, it should be investigated whether voice focus can also modify oral-nasal balance in hypernasal speakers with cleft palate and other disorders. (C) 2016 S. Karger AG, Basel
Keywords: Voice focus; Oral-nasal balance; Hypernasality; Brazilian Portuguese speakers; Nasalance